2014
DOI: 10.1039/c4py00548a
|View full text |Cite
|
Sign up to set email alerts
|

Dual-cure photochemical/thermal polymerization of acrylates: a photoassisted process at low light intensity

Abstract: The synergistic effect in dual-cure polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…This prevents further oxygen inhibition of the deepest layer, a fact that promotes the thermal polymerization. Consequently, the polymerization of the resin is accelerated under UV light [21].…”
Section: Dual-cure Photochemical / Thermal Initiating Systemmentioning
confidence: 99%
“…This prevents further oxygen inhibition of the deepest layer, a fact that promotes the thermal polymerization. Consequently, the polymerization of the resin is accelerated under UV light [21].…”
Section: Dual-cure Photochemical / Thermal Initiating Systemmentioning
confidence: 99%
“…As example, the decrease of light penetration with increasing thickness represents a serious drawback for thick, pigmented coatings and fiber-reinforced composites. Therefore, the concept of dual-cure initiating systems based on both photo-thermal curing appears as a promising alternative to solve the issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Indeed, the combination of a photochemical polymerization promoting a thermal curing has rendered possible the curing of thick samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal process can also be used to complete the curing of the epoxide resin in shadowed areas, typically in the case of 3D parts. In the best cases, the photochemical process would also speed up the thermal curing to perform a photoinduced thermal frontal polymerization [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the diffusion of active centres, Sangermano and coworkers successfully prepared antistatic epoxy coatings with 1 wt% carbon nanotubes and a thickness of more than 1 cm through cationic photopolymerization. 16 Normally, for cationic photopolymerization, aer irradiation, the sample can have a long induction period and can remain quiescent for more than 1 h at [25][26][27][28] C without an appreciable change in appearance or viscosity. 22,23 Crivello's studies showed that the photopolymerization of many alkyl glycidyl ethers displayed a prominent induction period at room temperature as a result of the formation of long-lived, relatively stable secondary oxonium ion species that are formed as intermediates, through protonation of the monomer by photogenerated Brønsted acid.…”
mentioning
confidence: 99%
“…25,26 For our experiments, the temperature was measured by a type T thermocouple. The thermocouple, which was electrically insulated from the mixture with PFA Teon, was connected to a data logger (TP9008U, Toprie, Shenzhen, CT), which was set at a frequency of 1 Hz.…”
mentioning
confidence: 99%